EVALUATING TIN CASE CORRUPTION POTRAYAL IN THE JAKARTA POST: APPRAISAL FRAMEWORK - Hara, Nina Tiya; Siregar, Maysarah; Nurlela, Nurlela (BASIS (Bahasa dan Sastra Inggris), 2024)
The appraisal framework serves as the methodology to evaluate language in news articles, revealing journalists' and news media outlets’ nuanced expressions of attitudes, emotions, and engagement in their reporting. This study embarks on an exploration of the appraisal framework within a selection of four news articles from The Jakarta Post, each addressing the pervasive issue of tin case corruption, resulting in a staggering loss of 271 trillion Rupiah for Indonesia. This study employs a qualitative descriptive design, utilizing Martin and White's (2005) appraisal analysis framework within Systemic Functional Linguistics.  The appraisal theory is applied to examine the news outlet's language in reporting on corruption cases. The findings suggest a predominant utilization of heterogloss (30%) and judgement (25%) which indicates a multifaceted approach characterized by the incorporation of diverse viewpoints and critical evaluations towards the corruption unfolding in the tin case. Notably, monogloss (17.5%) and graduation (17.5%) also feature prominently, reflecting a balanced discourse that encompasses both singular perspectives and nuanced expressions of intensity. Additionally, the usage of appreciation (5%) and focus (5%) is comparatively minimal, suggesting a lesser emphasis on acknowledging positive actions or delineating specific aspects within the coverage. This research illuminates the relationship between journalistic language and public perceptions of corruption, highlighting the need for critical evaluation of media coverage to promote informed discourse and enhance anti-corruption efforts.